(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
From the point of view of Syrian journalists, the importance of the research lies in attempting to determine the journalists understanding the idea of rumours and their objectives and dangers in the Syrian news websites. The research is based on a descriptive analytical method. To a achieve the objectives of the research ,a complete questionnaire was filled out by eighty five journalists out of one hundred ones questioned in the coastal region. Statistics show that the Syrian news sites journalists depend to some or maybe agreat degree on rumours that may or may not ,according to them, cause danger to society .Only experts can know whether rumours are pure rumour or not . The study proposes introducing legislations and laws that clarify the way and work that should be done by journalists, and also there should be criteria used in news sites.